Environmental management of filming in the City of Cape Town : a baseline study report & a draft situation analysis - Kowalyk, Jennifer; Rose-Innes, Olivia (Department of Environmental and Geographical Science, 2024)
The City of Cape Town has become increasingly important as a venue for filming activities, particularly since the mid to late 1990s. The area is attractive to film companies because it offers a considerable diversity of locations (many of great natural beauty) within a small geographic area; favourable weather; the availability of sunny locations during northern hemisphere winters; good film crews; sound infrastructure and accommodation; and better production value given that the cost of filming in South Africa is still highly competitive by international standards. Cape Town's economy benefits significantly from the film industry, which was estimated as having spent close to R500 million in total expenditure over the last year (Yutar, 2001). This puts the film industry as second only to tourism in terms of income generation. The industry is growing rapidly: between October 2000 and the end of March 2001 there were 1 530 shoots, compared with 911 during the same period a year earlier (Yutar, 2001 ). Toe industry also promotes Cape Town - particularly as a tourist destination - through international media exposure. This encouraging financial news, however, has been offset for many locals by the inconvenience and disturbance caused by filming activities such as closed roads, and the threat to the tranquility and quality of life in Cape Town. The challenge for environmental management is to find ways to continue to attract film-making and its much-needed revenue to the area, without compromising Cape Town's unique natural and socio-cultural character. As part of the attempt to meet this challenge, the City of Cape Town Environmental Management Department has commissioned Yebo Environmental Services and Environmental Science Masters students from the University of Cape Town to conduct a Baseline Study and Situation Analysis of Environmental Management of Filming Activities in the City of Cape Town. Toe latter will include recommendations for future management. Toe Baseline Study Report aims to provide an overview of the current situation and identification of key issues to inform the Draft Situation Analysis, which will be presen1ed at a stakeholder workshop on 11 May 2001. The Baseline Study Report and the Draft Situation Analysis are intended as documents that are linked but also "stand-alone.